2010 Integrated Communications, Navigation, and Surveillance Conference Proceedings 2010
DOI: 10.1109/icnsurv.2010.5503290
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of Multilateration Systems - a solution to nextgen surveillance

Abstract: Multilateration (MLAT) surveillance is now being used in all types of airspace for air traffic management. MLAT can be used for airport surface movement surveillance as well as for terminal and en route surveillance, using Wide Area Multilateration (WAM). MLAT is a low-cost technology that not only has major advantages in operations and maintenance, but also provides excellent performance under all conditions, especially for countries with large geographic areas or mountainous terrain to cover. This paper focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition, this location information can be used in conjunction with ADS-B and radar to provide an alternative solution when the navigation system fails. Figure 6 shows the TDOA [46].…”
Section: A Secure Location Verificationmentioning
confidence: 99%
“…In addition, this location information can be used in conjunction with ADS-B and radar to provide an alternative solution when the navigation system fails. Figure 6 shows the TDOA [46].…”
Section: A Secure Location Verificationmentioning
confidence: 99%
“…A data fusion architecture for air traffic control applications based on the radar plot and ADS-B was proposed in [12]. MLAT can be used for airport surface movement surveillance as well as terminal and en route surveillance using WAM according to [13]. In [14], the regularization method was proposed to solve the location problem of MLAT by mode S. Various applications of mode S for air traffic and airport traffic management were explored in [15], and multi-sensor data fusion was even used to help reduce sensor failure risk in [16].…”
Section: Related Workmentioning
confidence: 99%
“…Within different WSN or wireless positioning methods, it can be found that the multilateration method is frequently discussed and widely used [15,16]. Figure 1 shows the schematic diagram of the conventional multilateration method.…”
Section: Conventional Multilateration Positioning Methodsmentioning
confidence: 99%
“…In the WSN positioning methods, the received signal strength indicator (RSSI) information is often used to measure the distance between the beacon node and the target node, which can be expressed by [16] …”
Section: Proposed Multilateration Positioning Methods Based On Stochasmentioning
confidence: 99%
See 1 more Smart Citation